France : Financial Sector Assessment Program-Technical Note-Macroprudential Policy Framework and Tools. (IMF Staff Country Reports; Country Report ;, 2019)
This technical note on macroprudential policy framework and tools on France highlights that the institutional arrangements provide adequate powers to ensure Haut conseil de stabilite financiere's (HCSF) ability to act; however, some tools remain outside its legal domain. The report also discusses that The HCSF should evaluate effects of tools introduced to mitigate risks from corporate leverage. The HCSF should continue to monitor vulnerabilities in the corporate sector and once enough data is available, evaluate the impact on the tools introduced on: resilience of the financial system; and corporate borrowing behavior. A sectoral systemic risk buffer, calibrated to corporate exposures, could be considered if vulnerabilities intensify. A fiscal measure that incentivizes corporates to finance through equity rather than debt would affect both bank and market-based finance. Such a measure would have an impact on the demand for credit, rather than its supply. The macroprudential policy toolkit should be strengthened further.